A highly efficient intumescent polybutylene succinate: Flame retardancy and mechanistic aspects. (February 2022) - Xiao, Fei; Fontaine, Gaëlle; Bourbigot, Serge
Highlights: An intumescent system based on melamine poly(aluminum phosphate) and ethylenediamine phosphate. Combination of the intumescent system and zinc borate for superior fire performance. At 10% loading, significant reductions of pHRR (−63%), FIGRA (−43%), and MARHE (−48%). Abstract: A new strategy was developed for the fabrication of intumescent flame retardant system to improve the fire performance of polybutylene succinate (PBS) based on the synergistic effect of ethylenediamine phosphate (EDAP) and melamine poly(aluminum phosphate) (MPAlP) as well as zinc borate (ZnB). Cone calorimetry results exhibited that, with only 10 wt.% total loading of additives, the peak heat release rate (pHRR) and total heat release (THR) of PBS/EDAP&MPAlP(7:3, 8%)/ZnB(2%) were significantly reduced by 63% and 13%, respectively, in comparison to PBS. Meanwhile, the fire growth rate index (FIGRA) and maximum average rate of heat emission (MARHE) were decreased by 43% and 48% respectively, and its flameout time reached up to 840 s from 493 s for neat PBS. It should be noted that solid-state MAS NMR ( 11 B, 13 C, 27 Al, and 31 P) technique provided information to determine chemistry in the condensed phase during combustion. It was evidenced that the combination of EDAP/MPAlP and ZnB led to the formation of a protective intumescent char embedded with highly thermally stable phosphate species ( e.g., boron phosphate and zinc phosphate). They improved the cohesion (crack-free) and stability as well as the resistance of the char, thus improving the fire retardancy of PBS. Additionally, PBS/EDAP&MPAlP(7:3, 8%)/ZnB(2%) showed low smoke emission and good thermal/mechanical properties, thanks to the introduction of zinc borate. As a result, this work provides a new perspective for the development of new intumescent flame retardant systems toward PBS. Graphical abstract: Image, graphical abstract